Internalizing Ukhuwah Islamiyah Values in Junior High Schools at TMI Female Al-Amien Prenduan: Case Study of Bullying Behavior - Afifah Tijani; Rima Lailatul Husnah (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
Bullying is a person's negative behavior towards other people that causes uncomfortable or hurt and occurs repeatedly. Bullying behavior can occur in various places, one of which is the Al-Amien Prenduan Islamic Boarding School, especially in female junior high schools. Therefore, the Islamic boarding school tries to minimize this by maximizing the role of those who are directly involved with the students, namely the homeroom teacher. This research aims to describe the role of the homeroom teacher in internalizing the values of ukhuwah Islamiyah among junior high school students at TMI female Al-Amien Prenduan, efforts to deal with bullying, and its impact. This study uses a qualitative approach with data collection methods of observation, interviews, and documentation of homeroom teachers and students. Data analysis is done by reducing data, presenting data, and drawing conclusions. While the technique used to check the validity of the data is the triangulation technique. The results of this study indicate that the homeroom teacher has an important role in internalizing the values of ukhuwah Islamiyah so that the bullying behavior of junior high school students at TMI Female Al-Amien Prenduan is reduced.